Analysis of Microplastics on Digestive and Respiration System of Horse-Eye Jack Fish (Caranx latus) in Coastal Bungus Bay, West Sumatra - Fitri Yuranda; Zulkarnaini Zulkarnaini; Shinta Silvia; Calysta Deli Ad’hani (Jurnal Penelitian Pendidikan IPA, 2024)
Microplastic pollution accumulates in the marine environment, thus impacting the health of marine organisms. The purpose of this study was to analyze and identify the abundance and characteristics of microplastics in Horse-Eye Jack fish (Caranx latus) in coastal Bungus Bay, West Sumatra. Fish samples were taken at three different locations, namely, Sako beach, Caroline Beach, and the east side of Bungus Bay. The average abundance of microplastics in horse-eye Jack fish samples in digestive is 21.63 ± 3.99 particles/fish, and in respiration, 9.23 ± 1.92 particles/fish. The shape identified forms of microplastics are fibers, films, fragments, granules, and foam, and the dominant color of microplastics is red. The most common size of microplastics found was <0.5 mm. FT-IR spectroscopy analysis showed that the polymer types of microplastics found were PE, PVC, PET, and PS. Statistical tests showed differences between the abundance of microplastics in two pathways of microplastic uptake (digestive and respiration), and the sampling location P<0.05. The results showed that microplastics were found in all Horse-Eye Jackfish samples in Bungus Bay, West Sumatra.These findings highlight microplastics' harm to the marine ecosystem and the necessity of managing plastic waste if we hope to avoid future plastic pollution catastrophes